The Cambridge Pericope. The Addition to Luke 6.4 in Codex Bezae - Bammel, Ernst (New Testament studies, 1986)
Cambridge people, incorrigible as they are, like to sing the praises of Cambridge. Sharing this obligation I select a subject that may be in tune with this theme. As a New Testament man I do not have to compass land and sea in order to find an association. What may fairly be described as a unique challenge given by Cambridge to New Testament studies is to be found in the University library. It is what may be called the pericope Cantabrigiensis, the addition to Luke 6. 4 in the Codex Bezae Cantabrigiensis, which runs as follows: On the same day he saw someone working on the Sabbath and said to him: man, if you know what you are doing, you are blessed, if you do not know, you are cursed and a law-breaker (τυτ ⋯μέρᾳ θεασάμενός, τιναᾳγαζόμενον τ σαββάτ επεναυτ ἅνθρωπε ε μįν οδας τί ποιεις, μακάριος ε ε δį μεοįδας, ᾳπικατάρατος κᾳι παραβάτης ε τοū νόμον).